Synthesis of sec.-undecyl and sec.-dodecyl phenols as valuable intermediates of non-ionic surfactants (Bangladesh Journal of Scientific and Industrial Research, 2015)
The reaction of phenol with undecan-1-ol and dodecan-1-ol respectively was investigated in the presence of p-toluenesulphonic acid to get the corresponding alkylated phenols. The effects of the variation of different reaction parameters viz. temperature, molar ratio of phenol to undecan-1-ol and dodecan-1-ol respectively, amount of p-toluenesulphonic acid, addition of time and stirring of time on the reaction were studied and optimum conditions of the reaction were determined. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.22001 Bangladesh J. Sci. Ind. Res. 49(2), 85-88, 2014